Znaczenie zasady subsydiarnoścci dla rozwoju społeczeństwa obywatelskiego - Grabowiec, Piotr (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The return of the subsidiarity principle in the process of shaping a new image of Europe brings a fresh the ‘old thinking’ to whichWestern civilization has contributed. subsdiarity principle was applied under different social and political circumstances. The focal point of the subsidiarity principle is a human – an individual with his social nature and potential for shaping the space around him. Considering the values and features of the subsidiarity principle it has to be acknowledged that the republican ideals of civic society combined with the liberal considerations of Scottish moralists, concentrated in Tocqueville’s concept, provide the best grounds for the implementation of this principle.